DESCRIPTION OF UREUM AND CREATININE LEVELS IN MENOPAUSE WOMEN IN THE PUSKESMAS AREA KOTA SELATAN KOTA GORONTALO - Siti Nurkhalisah Mertosono Mertosono; Yusri Halada; Yolan Dunggio (LPPM Universitas Bina Mandiri Gorontalo, 2021)
In menopausal women, due to decreased ovarian function, the hormone estrogen produced by the ovaries will decrease so that there is a decrease in uric acid excretion in the blood through the kidneys and result in the accumulation of uric acid in the blood. Uric acid levels in the body form crystals that accumulate and can turn into kidney stones, which will cause a person to experience impaired kidney function. One of the renal function tests is urea and creatinine. The purpose of this study was to determine the description of urea and creatinine levels in menopausal women in the Puskesmas Kota Selatan area. This research uses descriptive quantitative research methods. The population of menopausal women was 387 people with a total sample of 20 people using a spectrophotometer. This research was processed through the IBM SPSS Statistics V25.0 program. The results of urea examination at menopause showed that the results of high urea levels were (60.0%) and normal (40.0%) as well as the results of the creatinine examination at menopause showed that the high creatinine results were (60.0%) and the normal ones were ( 40.0%). Based on the results of the study, it can be concluded that menopause with high urea and creatinine results is more than normal. It is recommended that menopausal women need to have a healthy lifestyle.